The Role of Sperm Protamine in Pathogenesis of Male Infertility - marzieh tavalaee; razieh ghorbani; mohammad hossein Nasr-Esfahani (Fasa University of Medical Sciences, 2019)
Background & Objective: Approximately 40-50% of infertility is due to male factor infertility that abnormal sperm chromatin structure as a major cause of infertility has been suggested. Protamines are the major components of sperm chromatin and play a central role in the correct chromatin packaging. Several studies have shown that the protamine deficiency in sperm is associated with low sperm quality and infertility. Considering the importance of protamine infertility, the purpose of this review article was to study the protamine content and it's biological significance in male fertility. Materials & Methods: Published papers by researchers in the Google Scholar, Science Direct and PubMed databases were collected from 1874 to 2018, and the best and most efficient papers were considered for this study. Results: Several studies have shown that there is a significant reverse relationship between protamine deficiency in sperm with fertilization and pregnancy rate following assisted reproduction techniques and central cause of protamine deficiency in sperm is due to the increase of oxidative stress which consequently causes to DNA damage. Conclusion: Treatment with antioxidants can reduce oxidative stress in infertile men, and improve sperm parameters, sperm protamine content, and DNA integrity.